Analisis Penerapan Integrated Marketing Communication (IMC) pada Produk Kur Mikro (Studi Kasus Bank Syariah Indonesia KCP Binjai Sudirman) - Husna Rangkuti, Munafiatul; Jannah, Nurul (Regress: Journal of Economics & Management, 2022)
This study uses a qualitative method with a case study approach. Where this study uses four informants. Data collected through observation, interviews, and documentation. From the results of the research conducted, it can be concluded that Bank Syariah Indonesia KCP Binjai Sudirman uses a marketing communication strategy for Kur Mikro products, in this case using marketing communications consisting of advertising, sales promotion, public relations, personal selling, and direct marketing to the field. Where in the implementation of the strategy carried out using various kinds of tools from each marketing communication instrument that is applied.